Comparative Analysis of Theories and Features of Venture Financing - Suleymanzade, Suleyman (Acta Universitatis Danubius. Œconomica, 2024)
The article examines various theories and models of venture financing. Theories and models are analyzed and compared, highlighting their advantages and disadvantages. The characteristics, specifics, and features of each venture financing theory are presented. Different stages, elements, and mechanisms of each theory and model of venture financing are explored. The significance of each theory and model is interpreted by identifying their positive and negative aspects. Features of the financial mechanism of venture investments are characterized. The direction of financial flows and the specifics of venture investments in the high-tech market are described.